2011
DOI: 10.1089/met.2010.0019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metabolic Syndrome on Cardio-Ankle Vascular Index in Middle-Aged and Elderly Chinese

Abstract: Metabolic syndrome is characterized by multiple risk factors and is associated with increased risk of diabetes and cardiovascular disease. The rapid change in the lifestyle and food habits of Chinese people has resulted in metabolic syndrome becoming one of the most widespread health challenges in China. Recently, the cardio-ankle vascular index (CAVI) was developed as a new parameter reflecting arterial stiffness and providing an index of vascular status. The purpose of this study was to investigate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 33 publications
6
26
3
1
Order By: Relevance
“…In our MS subjects, higher CAVI values were significantly associated with increased fasting and OGTT glucose levels, but we did not demonstrate an association between CAVI and insulin resistance and sensitivity indices, thus suggesting that glycaemia per se has the greatest impact on the arterial wall. We did not observe a significant relationship between higher CAVI scores and elevated waist circumference, which, at first glance, contradicts some findings from previous studies [22,23]. Liu et al reported that CAVI was significantly higher in subjects with abnormal waist circumference compared to normal subjects (P < 0.01) [23].…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…In our MS subjects, higher CAVI values were significantly associated with increased fasting and OGTT glucose levels, but we did not demonstrate an association between CAVI and insulin resistance and sensitivity indices, thus suggesting that glycaemia per se has the greatest impact on the arterial wall. We did not observe a significant relationship between higher CAVI scores and elevated waist circumference, which, at first glance, contradicts some findings from previous studies [22,23]. Liu et al reported that CAVI was significantly higher in subjects with abnormal waist circumference compared to normal subjects (P < 0.01) [23].…”
Section: Discussioncontrasting
confidence: 83%
“…We did not observe a significant relationship between higher CAVI scores and elevated waist circumference, which, at first glance, contradicts some findings from previous studies [22,23]. Liu et al reported that CAVI was significantly higher in subjects with abnormal waist circumference compared to normal subjects (P < 0.01) [23]. It has been reported that reducing weight is important for improving CAVI [35,36], and even short-term weight reduction may reliably decrease CAVI values (P = 0.015) [22].…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Atherosclerosis cases are increasing as influenced by a Westernized lifestyle [141][142][143]. Finally, in middle-aged and elderly Chinese living in northeast China, there was a higher incidence of MetS and cardiovascular disease, especially atherosclerosis [144].…”
Section: Metabolic Syndromementioning
confidence: 99%